(untitled) (Journal of Universal Science Research, 2026)
The article presents the results of theoretical and practical experiments on the improvement of the seed delinter. The upper chambers of the existing seed delinter are multi-faceted, and the use of combined saw-metal brush cylinders in them allows the extraction of fluff instead of fluff from dehaired seeds, and a technical solution for its implementation has been developed. It was determined that if the short fibers scraped off in the upper chamber of the delinter move along the surface of the combined saw-metal brush cylinder, the fibers in such a mass will remain on the surface of the combined saw-metal brush cylinder, and if they do not, such short fibers will separate from the surface of the combined saw-metal brush cylinder and turn into free fibers. In the conducted multi-factor experiments, the optimal parameters of the delinter were obtained.